Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1371/journal.pone.0123342
|View full text |Cite
|
Sign up to set email alerts
|

Differential Transcriptional Profiling of Damaged and Intact Adjacent Dorsal Root Ganglia Neurons in Neuropathic Pain

Abstract: Neuropathic pain, caused by a lesion in the somatosensory system, is a severely impairing mostly chronic disease. While its underlying molecular mechanisms are not thoroughly understood, neuroimmune interactions as well as changes in the pain pathway such as sensitization of nociceptors have been implicated. It has been shown that not only are different cell types involved in generation and maintenance of neuropathic pain, like neurons, immune and glial cells, but, also, intact adjacent neurons are relevant to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 33 publications
(38 reference statements)
6
40
0
Order By: Relevance
“…Indeed, ADAMTS-5 can be expressed by DRG neurons [24, 25] and chondroitin sulfate proteoglycans have been shown to interact with peripheral nerves [26]. We demonstrated that there was no acute effect of ADAMTS-5 treatment on mechanical allodynia (Fig 3B), but long-term effects cannot be ruled out and future work will seek to understand this in greater detail.…”
Section: Discussionmentioning
confidence: 72%
“…Indeed, ADAMTS-5 can be expressed by DRG neurons [24, 25] and chondroitin sulfate proteoglycans have been shown to interact with peripheral nerves [26]. We demonstrated that there was no acute effect of ADAMTS-5 treatment on mechanical allodynia (Fig 3B), but long-term effects cannot be ruled out and future work will seek to understand this in greater detail.…”
Section: Discussionmentioning
confidence: 72%
“…Thus, we expect OTOP channels are restricted to cell types that use changes in intracellular pH for cell signaling or to regulate biochemical or developmental processes. Along with a role in formation of vestibular otoconia (14), OTOP1 has been shown to protect mice from obesity-induced metabolic dysfunction (15), and it is upregulated in dorsal root ganglion cells in response to cell damage (20). The knowledge that this gene family encodes proton channels can be used to understand its contribution to physiology and disease.…”
mentioning
confidence: 99%
“…39,40 Overexpression of Atf3, as part of the inducible nerve RAG response, along with its “effector” RAGs, Sprr1a, and Gal, has been observed previously following both facial nerve damage 41 and sciatic nerve injury 42 in mice. Atf3 mutant mice have decreased neurite outgrowth on primary DRG neurons.…”
Section: Discussionmentioning
confidence: 73%